Unmasking mutual recognition : current inconsistencies and future chances - Wolfgang Kerber; Roger van den Bergh (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2007)
The principle of 'mutual recognition' is almost universally acclaimed for removing barriers to trade (e.g., within the EU), for enabling regulatory competition, and for preserving scope for regulatory autonomy instead of embarking on a path to harmonisation and centralisation. Through the analysis of the application of 'mutual recognition' within the EU (by using economic theories of legal federalism and regulatory competition), we show that this principle leads to a number of serious inconsistencies and problems, which question its suitability as a conflict of law rule that leads to a stable allocation of regulatory powers within a two-level system of regulations. 'Mutual recognition' should be understood more as a dynamic principle, which triggers a reshuffling of regulatory powers between different jurisdictional levels. It leads either back to the country of destination principle, to a free (internal) market for regulations, or to harmonisation and centralisation. In particular, the European experiences suggest that the introduction of a regime of 'mutual recognition' seems to be primarily another path to convergence and harmonisation instead of being an instrument that preserves decentralised regulatory powers or even regulatory competition.
Keywords: 330